1988
DOI: 10.1302/0301-620x.70b1.3339061
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular fluid pressure and pain in osteoarthritis of the hip

Abstract: We investigated the relationship between the pain experienced by 50 patients with osteoarthritis of the hip and the resting intra-articular pressure of the synovial fluid. We found a significant linear correlation between these factors, greater pain being experienced by patients with higher pressures. In 20 cases we showed that the pressure rises in extension and medial rotation and is least in flexion and mid-abduction. These results help to explain the benefits of rotation osteotomy of the hip and of psoas r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 5 publications
2
41
2
1
Order By: Relevance
“…In primary arthrosis and several other hip disorders, there is a correlation between increased intracapsular pressure and pain (Goddard andGosling 1988, Robertsson et al 1995). A similar correlation may exist in cases with a loose hip prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In primary arthrosis and several other hip disorders, there is a correlation between increased intracapsular pressure and pain (Goddard andGosling 1988, Robertsson et al 1995). A similar correlation may exist in cases with a loose hip prosthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Effusion causing distension of the capsule andlor increased intracapsular pressure has been observed in several hip disorders, such as arthrosis (Timofeeva 1975, Goddard and Gosling 1988, Robertsson et al 1995, transient synovitis (Kloiber et al 1983, Wingstrand et al 1985a, septic arthritis (Wingstrand et al 1987) and juvenile chronic arthritis (Rydholm et al 1986). …”
Section: Lntracapsular Pressure and Loosening Of Hip Prostheses Preopmentioning
confidence: 99%
“…One hypothesis of the etiology of arthrosis is that initially synovitis causes increased intraarticular pressure Reimann 1979, Goddard andGosling 1988) leading to increased intraosseous pressure, which has been found in advanced arthrosis of the hip (Amoldi et al 1972, Termansen et al 198 1, K i m et al 1988), but not in early arthrosis of the knee (Arnoldi et al 1975). However, we found normal pressures in our cases of early coxarthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…as well as in nontraumatic necrosis of the femoral head (Arlet and Durroux 1973, Ficat and Arlet 1979, Inoue and Ono 1979, Jacqueline and Rutishauser 1971. Intraosseous blood circulation has been evaluated indirectly by measuring intraarticular pressure (Goddard and Gosling 1988), intraosseous pressure (Amoldi et al 1972, Ficat andArlet 1979, Termansen et al 198 l), and intraosseous blood gas tensions (Kim et al 1986(Kim et al , 1988. These studies indicate that hypoxiadue to intramedullary stasis is of pathogenetic importance in both conditions.…”
Section: Int Raosseous Pressure Oxygenat Ion and Histology Inarthromentioning
confidence: 99%
“…6,7,9 A positive correlation between the pain score and IAP was identified in a previous study. 10 Joint injury has also been observed with high IAP. 6,9,10 Many studies have investigated the IAP of the shoulder, 2À4,8,11,12 hip 10,13,14 as well as knee joints, 7,9,15À18 and it has been found that negative IAP is a passive stabilizer during joint movement.…”
Section: Introductionmentioning
confidence: 99%